(untitled) (Eurasian Journal of Ecology, 2016)
The paper covers the main results of the study of radionuclide and elemental composition of water, sediment and soil samples collected at the border areas of the following transboundary rivers in Kazakhstan: Chagan, Ural, Ilek, Tobol,Ayat, Irtysh, Emel, Ili, Tekes, Shu, Karabalta, Talas, Syrdar’ya. The analyses were performed using the methods of instrumental gamma-spectrometry (IGS), radiochemical analysis (RCA), neutron-activation analysis (NAA), X-ray fluorescence analysis (XRF) and inductively coupled plasma mass spectrometry (ICP- MS). The IGS, NAA and XRF data revealed high content of natural radionuclides (NRN) and certain elements in soil and/or bottom sediments of the following rivers: Ili, Tekes, Shu, Karabalta, Talas, Syrdar’ya – all NRN such as Ca, Sc, As, Rb, Sr, Sb, Ba, Th,U; Ural, Chagan, Ayat – Cr, Ni, Co; Shu, Irtysh (on the border with Russia) – Zr, Hf, Ta. On the basis of RCA, NAA and ICP-MS we revealed the high content of impurities in water of the following rivers: Shu, Emel, Talas, Syrdar’ya and especially Karabalta – U-234, U-238, Li, As, Se, Sr, Mo, Sb; Tobol, Ayat – Sc, Fe, Co, Ni, Zn, Br, Rb; Ilek (Aktobe region, “Tselinnoye” settlement) – Cr. To identify the sources and mechanisms of revealed contamination it is necessary to perform the survey of individual areas of these rivers on the territory of Kazakhstan and beyond.